When One's Life Becomes the Field: Assessing the Field in Collaborative Autoethnography - Leiwo, Lotta (Marburg journal of religion, 2024)
Autoethnography is an ethnographic research method that uses a researcher's own experiences as data. When an autoethnographic researcher's and ethnographic researcher's perspectives are brought together in collaborative autoethnography (CAE), the internal dialogues generated from the researcher's positions form more diverse analysis of the data. CAE studies personal experiences of the research subject within a culture to produce an ethnographic analysis of the cultural context and implications of the research topic. Conducting CAE demands careful ethical considerations and self-reflection. Being one's own research subject can be personally exhausting and professionally rewarding at the same time.This paper describes my autoethnographic process in a CAE project conducted with the folklorist Heidi Henriikka Mäkelä. In the case study, we examined forest yoga, affective practices, and the fracturing imageries of forest space in 2020s Finland. The study highlights personal experiences of forest yoga, and at the same time examines them in wider social contexts such as nationally interpreted forest imageries and feminism through an ethnographic dialogue.In ethnographic research, the whole research process is considered a field; however, the multifaceted concept of the field in CAE has remained vague. It is important to understand and outline the field when conducting (C)AE to be able to evaluate validity, reliability, and ethical questions regarding fieldwork. This paper discusses how field(s) were outlined in the case study and outlines benefits and challenges of the method. I argue that the experience of being a research subject provides embodied affective insight on these questions that cannot be achieved otherwise. Autoethnography is a means to achieve this knowledge.